STATUS OF ETHICAL REVIEW BOARDS AT ALL MEDICAL COLLEGES OF KHYBER PAKHTUNKHWA - Abrar, Saidul; Ronis, Katrina Aminah; Khan, Shahid; Siraj, Sumbal; Safdar, Wajeeha; Khalid, Yamna; Amjad, Ayesha; Akhtar, Sonia; Abdullah, Haleema; Alam, Tayeba; et al. (Journal of Ayub Medical College Abbottabad, 2015)
Background: Ethics means custom, character, habit or disposition and as a discipline is frequently called Moral Philosophy. Ethics cannot be regulated until it is incorporated in Law. With the advent of research in life sciences, the need of ethical review boards was felt to protect individual and public interests. The objective of this study was to know the status of ethical review boards at all medical colleges of Khyber Pakhtunkhwa in terms of its existence, membership and activities. Methods: This province wise cross-sectional survey was conducted over a period of three months. All the sixteen medical colleges of the province registered with Pakistan Medical and Dental Council Islamabad were included. A structured questionnaire was used as data collection tool. Single respondent from each medical college was identified by the respective chief executive officer or principal. Data was analysed through SPSS V-20 and MS Excel 2007. Descriptive statistics were calculated for quantitative data. Results: Out of sixteen medical colleges, one had no ethical review board and another neither refused nor returned filled questionnaire. Eleven medical colleges reported combined boards with their teaching hospitals, while 3 had separate boards. Highest number of members noted was 14 and lowest being 4. Mode was 8. None of the boards had a medical doctor with degree or diploma in bioethics, as its member. Six medical colleges had medical doctors who had attended workshops on bioethics. Majority of medical colleges had no track of record about its review boards. Conclusion: Overall situation of ethical review boards at the medical colleges of Khyber Pakhtunkhwa is not satisfactory and needs proper regulatory measures. Keywords: Institutional Review Board, Ethics Committee, Bioethics, Pakistan, Khyber Pakhtunkhwa